Synthesis and tailored properties of covalent organic framework thin films and heterostructures. (December 2021) - Beagle, Lucas K.; Fang, Qiyi; Tran, Ly D.; Baldwin, Luke A.; Muratore, Christopher; Lou, Jun; Glavin, Nicholas R.
Graphical abstract: Abstract: Porous polymeric covalent organic frameworks (COFs) have been under intense synthetic investigation with over 100 unique structural motifs known. In order to realize the true potential of these materials, converting the powders into thin films with strict control of thickness and morphology is necessary and accomplished through techniques including interfacial synthesis, chemical exfoliation and mechanical delamination. Recent progress in the construction and tailored properties of thin film COFs are highlighted in this review, addressing mechanical properties as well as application-focused properties in filtration, electronics, sensors, electrochemistry, magnetics, optoelectronics and beyond. Additionally, heterogeneous integration of these thin films with other inorganic and organic materials is discussed, revealing exciting opportunities to integrate COF thin films with other state of the art material and device systems.